PENGARUH REVIEW PRODUK DAN IKLAN SEBAGAI MEDIA PEMASARAN TERHADAP MINAT KONSUMEN PADA SCARLETT WHITENING - Aisya Fatmala (ECONOMOS, 2022)
Modern technology today makes people get information faster, every day always comes the latest information and new products, especially through social media. Such as the latest fashion information, household needs, and various body care. Body care is one of the needs of the community that is currently loved and sought after like Scarlett Whitening products. Through social media makes it easier for people to get product information that is searched along with product ads that can encourage buying interest. Therefore, this study was conducted to find out if there is an influence between product reviews and advertising on consumer interest in scarlett whitening products. This study is aimed at respondents who have seen or watched reviews and advertisements of scarlett whitening products with non-problability sampling methods of purposive sampling type. The research method used is a quantitative method where the analysis technique uses correlation analysis with the SPSS software assistance. From the results of this study it is known that product reviews and advertisements have a significant influence on consumer interests.